Analysis of Loyalty and Fanatism Factors in the Psyhco Sociologys of Psim Jogja Supporters Throughout the Anthem Aku Yakin dengan Kamu - Wibiyanto, Agung; Syaifullah, Jahid; Dani, Jeratallah Aram; Sudarmaji, Sudarmaji (Riwayat: Educational Journal of History and Humanities, 2025)
In writing this article will review the analysis of loyalty and fanaticism factors in the Psycho Sociology of PSIM Jogja supporters tucked away in the Anthem "Aku Yakin Dengan Kamu". The research method used is a qualitative method with descriptive analysis, where data sources obtained from journals and books will be processed and reduced into a writing. The results of this article emphasize in the anthem "Aku Yakin Dengan Kamu" seen in full how in the lyrics of the song there is certainly a spirit that will be built by PSIM Jogja supporters which is accumulated in the context of fanaticism that can be realized in several products produced such as those directly related to the PSIM Jogja club whether it is merchandise, match tickets or even interesting content created on social media related to PSIM Jogja. So, it is very clear from the manifestation of the increasing expression of fanaticism, starting from excessive love for their favorite football team to actualization in the behavior of purchasing or using their football team attributes. By looking at this context, it has been very clear that fanaticism has been able to encourage football teams to spend their money to get merchandise on the team they support. But on the other hand, the psycho-sociological condition of PSIM Jogja supporters, the fanaticism that exists leads to social friction that ends in chaos with other community groups, especially other supporter groups considering that many supporter groups come from the lower middle class and they really need entertainment.